Visceral adipose tissue volume is associated with premature atherosclerosis in early type 2 diabetes mellitus independent of traditional risk factors. (November 2019) - Reijrink, Melanie; de Boer, Stefanie A.; Spoor, Daan S.; Lefrandt, Joop D.; Lambers Heerspink, Hiddo J.; Boellaard, Ronald; Greuter, Marcel JW.; Borra, Ronald J.H.; Hillebrands, Jan-Luuk; Slart, Riemer H.J.A.; Mulder, Douwe J.
Abstract: Background and aims: Type 2 diabetes mellitus (T2DM) is commonly associated with abdominal obesity, predominantly with high visceral adipose tissue (VAT), and is accompanied by premature atherosclerosis. However, the association between VAT and subcutaneous adipose tissue (SAT) with premature atherosclerosis and (i.e. arterial) inflammation is not completely understood. To provide more insight into this association, we investigated the association between arterial 18 F-fluordeoxyglucose (FDG) positron emission tomography (PET) uptake, as a measure of arterial inflammation, and metabolic syndrome (MetS) markers in early T2DM patients. Methods: Forty-four patients with early T2DM, without glucose lowering medication, were studied (median age 63 [IQR 54–66] years, median BMI 30.4 [IQR 27.5–35.8]). Arterial inflammation was quantified using glucose corrected maximum standardized uptake value (SUVmax ) FDG of the aorta, carotid, iliac, and femoral arteries, and corrected for background activity (blood pool) as target-to-background ratio (mean TBR). VAT and SAT volumes (cm 3 ) were automatically segmented using computed tomography (CT) between levels L1-L5. Non-alcoholic fatty liver disease (NAFLD) was assessed by liver function test and CT. Results: VAT volume, but not SAT volume, correlated with mean TBR (r = 0.325, p =  0.031). Linear regression models showed a significant association, even after sequential adjustment for potentially influencing MetS components. Interaction term VAT volume * sex and additional components including HbA1c, insulin resistance, NAFLD, adiponectin, leptin, and C- reactive protein (CRP) did not change the independent association between VAT volume and mean TBR. Conclusions: CT-assessed VAT volume is positively associated with FDG-PET assessed arterial inflammation, independently of factors thought to potentially mediate these effects. These findings suggest that VAT in contrast to SAT is linked to early atherosclerotic changes in T2DM patients. Highlights: T2DM patients with increased VAT volume are at risk for premature atherosclerosis. VAT volume is positively associated with arterial inflammation in early T2DM. Premature atherosclerosis was imaged with FDG and quantified as mean TBR. The association of VAT with mean TBR was independent of VAT dysfunction biomarkers.